Multi-Microcontroller Evaluation Tool for Education in Embedded Control Technology: The UMP-EVT - Selvakumar, Raja Saravana Kumar; Kamarul Hawari, Ghazali; Nik Mohd Kamil, Nik Yusof (2010)

(untitled)
In traditional Embedded Control Technology courses, students learn to develop assembly language programs to control peripherals, handle interrupts, and perform I/O operations. Designing and programming of embedded systems require skills that need training and practice. The main problem of such approach is its focus on only one device type with other microcontroller families requires other development boards. This aspect becomes important in a university laboratory, where students have to work with different types of embedded systems. For example, in our Faculty of Electrical & Electronics Engineering, three 8-bit are used in different projects. Each microcontroller type requires its own development board with its own set of peripheral devices; this is a waste of resources and so came the idea to use the same set of peripherals on a mainboard and to plug in an application board with a specific microcontroller and its associated circuitry. A new laboratory evaluation tool (UMP-EVT) specifically will be designed to be as a learning tool for those who intend to learn microcontroller and for use in the academic environment. One mainboard and three application boards were designed and tests were performed. In this respect, this UMP-EVT would be applicable for education and expose the electrical engineering students to the understanding fundamental of microcontroller in electronic design field. Keywords: Educational, MCS51 microcontroller, HC11 microcontroller, PIC microcontroller